Applications of Psychology in the Analysis of Consumer Behaviour – Selected Issues - Włodarczyk, Katarzyna (Zastosowania psychologii w analizie zachowań konsumentów – wybrane zagadnienia, 2023)
Psychology plays an especially significant role in the study of consumer behaviour, as it applies scientific research of human, social, cognitive and emotional factors in order to better understand the behaviour of individuals. The paper presents aspects of the use of psychology in contemporary studies of consumer behaviour. The aim was to indicate the current aspects of the use of psychology in consumer behaviour research and to indicate further directions of using psychology in relation to contemporary changes on the market. The paper features theoretical deliberations based on the literature of the subject.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 3, s. 142-152
Keywords: consumer behaviour; consumption; psychology; zachowania konsumentów; konsumpcja; psychologia